2007
DOI: 10.1007/s10544-007-9090-2
|View full text |Cite
|
Sign up to set email alerts
|

Ultrananocrystalline diamond film as an optimal cell interface for biomedical applications

Abstract: Surfaces of materials that promote cell adhesion, proliferation, and growth are critical for new generation of implantable biomedical devices. These films should be able to coat complex geometrical shapes very conformally, with smooth surfaces to produce hermetic bioinert protective coatings, or to provide surfaces for cell grafting through appropriate functionalization. Upon performing a survey of desirable properties such as chemical inertness, low friction coefficient, high wear resistance, and a high Young… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
69
0
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 113 publications
(75 citation statements)
references
References 17 publications
2
69
0
2
Order By: Relevance
“…The B-NCD thin films have been subject to a great deal of attention due to their outstanding properties, remarkable hardness, optical transparency in a broad wavelength [31,32], high thermal conductivity [33] as well as biocompatibility [34,35]. Unlike the rough polycrystalline films with grain sizes above 500 nm, NCD films with typical grain sizes and surface roughness of less than 100 nm are relatively smooth showing properties close to single crystal diamond [36].…”
Section: Introductionmentioning
confidence: 99%
“…The B-NCD thin films have been subject to a great deal of attention due to their outstanding properties, remarkable hardness, optical transparency in a broad wavelength [31,32], high thermal conductivity [33] as well as biocompatibility [34,35]. Unlike the rough polycrystalline films with grain sizes above 500 nm, NCD films with typical grain sizes and surface roughness of less than 100 nm are relatively smooth showing properties close to single crystal diamond [36].…”
Section: Introductionmentioning
confidence: 99%
“…Bajaj et al demonstrated that the rat pheochromocytoma cells were cultivated on different substrates, such as UNCD film, silicon and platinum and investigated the cell adhesion, proliferation and growth of the cell on those substrates [38]. As a result, the cell on the UNCD was suppressed by the hydrogen terminated NCD surface.…”
Section: Properties Of Nanocrystalline Diamondmentioning
confidence: 99%
“…Which indicates that the UNCD surface have much more biocompatibility compared to other surfaces. Finally the maximum cells attachment, cell spreading and nuclear area coverage of the cell in UNCD surface is much more compered to other surfaces [81]. In medical application DLC can coat over the stent.…”
Section: Diamond Dlc Dln For Biomedical Applicationsmentioning
confidence: 99%